HUBUNGAN KUALITAS INFORMASI VISUAL STATIS PADA AKUN INSTAGRAM @BERITA_LAMONGAN_ DENGAN MINAT BACA FOLLOWER - Nur Aisyah; Sukma Ari Ragil Putri (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This study discusses an effective communication process so that interaction and feedback are obtained from the communicant. This study aims to identify the relationship or influence of the quality of static visual information on the @berita_lamongan_ account on followers' reading interest. This research method is quantitative with explanatory survey methods and questionnaire research instruments as an alternative to data collection, so that data from respondents is collected and then analyzed. The object of the research is the Instagram account @berita_lamongan_. The research location is in Lamongan district with a population taken from followers of the @berita_lamongan_ account totaling 57.4 thousand followers. The sampling technique based on the Slovin formula obtained a sample of 100 respondents. To determine the relationship between these two variables, the researcher used the Chi-Square Test. While the questionnaire to process the test data used SPSS for Windows version 20. The grand theory used as the basis for the analysis was the Stimulus Organism Response from McQuail. a significant value of 0.000 from the Chi Square Test. So that Ho is rejected and Ha is accepted.